Frugivorous Flies on Bitter Gourd Fruit in Parigi Moutong Regency - Fatmah Dhafir; Manap Trianto (Jurnal Biologi Tropis, 2023)
In Indonesia, many people eat pariah as a vegetable. This plant can not only be consumed as a vegetable, but can also be used for medical purposes. Sample collection was carried out using purposive sampling technique. Samples taken were pariah fruits suspected of being infested by frugivorous fly pests. Sampling was done once in four different fields for each commodity. There were five types of frugivorous flies found on peria fruit, namely Z. cucurbitae, Z. calumniatus, Z. tau, A. Orientalis, and flies of the family Lonchaeidae species Silba sp. The highest proportion of flies found from peria fruit was Z. cucurbitae. The highest single percentage infestation of flies on peria fruit was A. orientalis. A. orientalis has the potential to infest fruit singly on peria fruit because it has the highest percentage of single infestation compared to other frugivorous flies. Parasitoids found were Psyttalia sp. and Fopius arisanus. Further research needs to be done on the single infestation of A. orientalis and Lonchaeidae, especially on peria fruit by inserting the flies into caged fruit at different maturity levels and varieties, so that it can be proven whether A. orientalis and Lonchaeidae can infest fruit singly on peria fruit and cucumber and how to control them so that the population level can be suppressed.